Out-of-band gain prediction of blade antennas for EMC purpose - Wang, Lu (2013)
In this paper, the out-of-band characteristics of the airborne blade antennas are studied in terms of their gain and radiation properties. A prediction model was derived for both the lower out-of-band and upper out-of-band frequencies of a typical blade antenna.